Charismatic Reformer, Mystic or Father? The Reception of Symeon the New Theologian by Pentecostal/Charismatic Theologians - Lysack, Maxym (Religions, 2021)
The last three decades have seen a renewed interest on the part of Evangelical scholars in patristic studies. Recently, theologians of the Pentecostal/Charismatic tradition have started to examine the works of Saint Symeon the New Theologian. The latter’s emphasis on personal experience of the Holy Spirit and Christification provides a fertile ground for encounter between Orthodox and Pentecostal/Charismatic scholars. Recent Pentecostal/Charismatic scholarship on Symeon is reviewed in the light of contemporary Orthodox scholarship. Four key moments in Symeon’s teaching on asceticism are presented in response to two Pentecostal/Charismatic theologians.